Smart Partnership between UMP and KBS to benefit Malaysian Youths - Siti Sarah, Mohamad Rajimi (2018)
Putrajaya, 13 December – Universiti Malaysia Pahang (UMP) has closed the deal with Ministry of Youth and Sports (KBS) in offering academic program for the Malaysian youth. Besides UMP, KBS also has signed memorandum of understanding with industry and other university in an event held at KBS office in Putrajaya.